High-speed atomic force microscopy. (August 2019) - Ando, Toshio
Abstract : High-speed atomic force microscopy (HS-AFM) is a unique tool for molecular imaging. It can directly visualize protein molecules during their functional activity at high spatiotemporal resolution, without a marker being attached to the molecules. Molecular dynamics filmed with HS-AFM can provide mechanistic insights into the functional molecular processes that are hard to be attained with other approaches. In this mini review, I highlight some of recent relevant studies of proteins by HS-AFM imaging after brief descriptions of AFM and HS-AFM.